ANALYSIS OF HOUSING LAND CARRYING CAPACITY IN THE DISTRICT PALARAN, SAMARINDA CITY EAST KALIMANTAN - Dedy Nugroho; yunianto setiawan; Abdul Kahar; Yohanes Budi Sulistioadi (Jurnal Infrastruktur, 2021)
Population growth has an impact on development in various sectors. One of the sectors affected is the housing sector. In determining the location of housing requires a complex analysis in order to create a decent housing area. In the 2014-2034 Samarinda City Spatial Plan, certain locations have been determined to become residential areas. Palaran sub-district was chosen and prepared to become a high-density residential area. In this study, an analysis was carried out on the power of shamans for residential land in Palaran District. The analytical technique used to determine the carrying capacity and adequate capacity for housing is the Land Carrying Capacity Analysis Method which has been stipulated in the Regulation of the Minister of Public Works No. 20/PRT/M/2007 and the Indonesian National Standard 03-1733-2004 concerning Residential environmental planning procedures. In the analysis process, the data used are the Samarinda City Spatial Plan in 2014-2034 and the Draft RDTR of Palaran District. In the analysis of the carrying capacity of the land, the results of the land capability are divided into 5 classes. High development capability 1.091,01 Ha; rather high development capability 3.463,87 Ha; medium development capability 2,742,79 Ha; low development capability 8,963,35 Ha; and very low capacity 2,394,37 Ha. Based on the results of the analysis, it is obtained a suitable location for housing development in Palaran District.